Successful Treatment of Focal Segmental Glomerulosclerosis after Kidney Transplantation with Plasma Exchange and Abatacept in a Patient with Juvenile Rheumatoid Arthritis - Hannelore Sprenger-Mähr; Emanuel Zitt; Afschin Soleiman; Karl Lhotta (Case Reports in Transplantation)
Recurrent focal segmental glomerulosclerosis (FSGS) after renal transplantation is difficult to treat. Recently a series of four patients unresponsive to plasma exchange (PE) and rituximab, who were successfully treated with abatacept, has been reported. We present a 26-year-old Caucasian patient who suffered from juvenile rheumatoid arthritis and developed severe proteinuria eleven days after transplantation. An allograft biopsy was suggestive of recurrent focal segmental glomerulosclerosis. He did not respond to PE therapy. A first dose of abatacept produced partial remission. Four weeks later proteinuria again increased and a second biopsy showed progression of disease. After another ineffective course of PE he was given a second dose of abatacept, which was followed by rapid, complete, and sustained resolution of proteinuria. This treatment caused a significant increase in BK and JC viremia. Whether abatacept ameliorated proteinuria via an effect on podocytes or on the patient’s primary disease remains speculative.